Chemical characterization and radiocarbon dating of the rock art of Las Charcas caves, Cuba. (18th December 2020) - Armitage, R. A.; Arrazcaeta, R.; Torres, S.; Baker, S. M.; Fraser, D.
Abstract : There has been much debate over the decades amongst Cuban archaeologists about what group or groups may have created the rock art in the karst caves of Cuba. The complexities of Cuba's history made dating rock paintings an attractive method for determining their origins. Samples were collected from three caves in Mayabeque province, collectively referred to as Las Charcas. Chemical analyses were carried out along with plasma–chemical oxidation and accelerator mass spectrometric radiocarbon dating. The paintings in two caves contained bitumen, resulting in anomalously old dates, whilst the other cave's amorphous carbon‐based paintings fit within a pre‐Columbian context.